2012
DOI: 10.1007/s13197-012-0757-1
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of postharvest chilling injury of tomato fruit by salicylic acid treatment

Abstract: Tomato fruit at the mature green stage were treated with salicylic acid at different concentration (0, 1 and 2 mM) and analyzed for chilling injury (CI), electrolyte leakage (EL), malondialdehyde (MDA) and proline contents and phospholipase D (PLD) and lipoxygenase (LOX) activities during cold storage. PLD and LOX activities were significantly reduced by salicylic acid treatment. Compared with the control fruit, salicylic acid treatment alleviated chilling injury, reduced electrolyte leakage, malondialdehyde c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In agreement with Mo et al (2008), we found that SA delays the ripening process by maintaining membrane integrity and decreasing ethylene production. In apples (Mo et al 2008) and tomatoes (Aghdam et al 2014), SA application increases the membrane integrity and firmness. Moreover, SA increases the Ca 2+ level in intercellular spaces and in plasma membranes of grape plants .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with Mo et al (2008), we found that SA delays the ripening process by maintaining membrane integrity and decreasing ethylene production. In apples (Mo et al 2008) and tomatoes (Aghdam et al 2014), SA application increases the membrane integrity and firmness. Moreover, SA increases the Ca 2+ level in intercellular spaces and in plasma membranes of grape plants .…”
Section: Discussionmentioning
confidence: 99%
“…So how can one prevent bananas from being damaged due to reactive oxygen species is an issue deserving serious consideration (Srivastava & Dwivedi, ). Salicylic acid (SA) is considered a vital signaling molecule which plays an important role in regulating disease resistance (Liu, Ma, Liu, Zhu, & Hao, ) and reducing the production rate of superoxide anions in fruits (Hao, ), such as kiwi (Fatemi, Mohammadi, & Aminifard, ), cherry (Dokhanieh, Aghdam, Fard, & Hassanpour, ), apple (Mo et al, ), tomato (Aghdam, Asghari, Khorsandi, & Mohayeji, ), mango (Pagadala Damodaram et al, ), and pear (Wang, Cao, Lin, Sun, & Jiang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Linolenic acid and linoleic acid are substrates of LOXs, and LOX activity is increased under low-temperature stress, resulting in a decreased content of linolenic acid and linoleic acid. Aghdam et al [14] found that the LOX activity increases when tomatoes are chilled. In tomato, chilling can improve the integrity of the cell membrane and enhance cold tolerance by reducing the activity of LOX [14].…”
Section: Analysis Of Cis-elements In Promoters Of Ftlox Genesmentioning
confidence: 99%
“…Aghdam et al [14] found that the LOX activity increases when tomatoes are chilled. In tomato, chilling can improve the integrity of the cell membrane and enhance cold tolerance by reducing the activity of LOX [14]. LOXs can contribute to the degradation of storage lipids during seed germination [39].…”
Section: Analysis Of Cis-elements In Promoters Of Ftlox Genesmentioning
confidence: 99%
See 1 more Smart Citation